Determinants of the Nordic hedge fund performance - Kolisovas, Danielius; Giriūnienė, Gintarė; Baležentis, Tomas; Štreimikienė, Dalia; Morkūnas, Mangirdas (Journal of Business Economics and Management, 2022)
Hedge funds have become an important part of the financial sector. The development of the hedge funds in the Nordic countries has been rather robust. Therefore, it is important to identify the determinants of the hedge fund performance and isolate the managerial performance, i.e., the Jensen’s alpha. To this end, this paper construct cross sectional and panel model for the Nordic hedge funds over 2005–2018. The Fung-Hsieh 8-factor model and other models are developed to identify the determinants of the Nordic hedge fund performance. The effects of crises of different nature (local to global, hedge funds to banking sector) are also tested. The results indicate that Nordic hedge funds are capable to generate positive alpha during the crisis even exceeding the alpha of the economically stable time periods.